Explosion at an aluminum factory caused by the July 2018 Japan floods: Investigation of damages and evacuation activities. (March 2021) - Araki, Yuko; Hokugo, Akihiko; Pinheiro, Abel Táiti Konno; Ohtsu, Nobuhito; Cruz, Ana Maria
Abstract: An explosion at an aluminum factory occurred due to floods in Soja City, Okayama Prefecture, in July 2018. This study investigates the accident, its overall impact on local residents, and emergency management activities. The results of the study showed that several nearby structures and homes were damaged by the explosion. Concern for more explosions has led to the evacuation of residents of Shimobara area of Soja City. In Shimobara, residents had carried out voluntary disaster prevention activities before the disaster. After the explosion, Shimobara residents were able to evacuate safely in cooperation with the voluntary disaster prevention organization and the local government agency. The study revealed that there was a lack of information on chemical accident hazards shared by the factory with local government authorities and first responders, as well as with local residents. In order to be better prepared for technological accidents, and in particular accidents caused by natural disasters (known as Natechs), mechanisms for information sharing between companies and municipalities should be adopted. Highlights: An explosion at an aluminum plant occurred due to floods in July 2018. Explosion risk was not shared from the factory to city government and residents. The explosion destroyed the neighboring houses and caused multiple fires. After the explosion, 300 neighbors evacuated outside the area in cooperation. Interviews with residents and city officials revealed the evacuation process.